An Executive Summary Explaining Virtual Technology Use to Educate Nursing Students in Population Health Concepts - Carpenter, Tristin; Cherry, Kim; Spencer, Jolene (My University, 2024)
This submission meets the university requirements for the DNP project.
Keywords: Virtual clinic; Population health; Community health; Simulation